Looking for empirical evidence about the socio-economic activity of countries with social accounting matrices - Santos, Susana (2016)
In looking for empirical evidence about the socio-economic activity of countries, a proposal is made for studying it through the use of Social Accounting Matrices (SAMs). SAMs are presented as tools that have specific features for conducting studies in several different areas, as well as for supporting policy decision processes. Based on methodological principles that are derived mainly from the works of Stone and Pyatt, emphasis is placed on the desirability of working in a matrix format, which simultaneously includes activities (or industries), products, factors of production and institutions. This is considered to be a way of capturing the relevant network of linkages and the corresponding multiplier effects in the subsequent modelling of the socio-economic activity of the countries studied. The exposition is accompanied by the example of a SAM applied to Portugal.